Dendrobium laoshanense (Orchidaceae; Epidendroideae), a new species from Yunnan, China - Zhang, Longping; Huang, Ye; Wang, Linying; Lan, Siren (Phytotaxa, 2026)
A new orchid species, Dendrobium laoshanense, from Yunnan, China, is described and illustrated in this study based on morphological evidence. Morphological analysis indicates that D. laoshanense is similar to D. hercoglossum and D. aduncum, but it can be distinguished from the former by a lip with a broader base that gradually narrows to an acute apex and bears dense yellow short hairs at the base, and from the latter by leaves that are apically obtuse and unevenly bilobed, together with narrower, more elongate sepals and petals, each with a hooked apical tip.